Extremely flexible and mechanically durable planar supercapacitors: High energy density and low-cost power source for E-skin electronics. (December 2020) - Yun, Yeonghun; Nandanapalli, Koteeswara Reddy; Choi, Ji-Hyuk; Son, Wonkyeong; Choi, Changsoon; Lee, Sungwon
Abstract: The development of multifunctional devices on highly flexible and biocompatible substrates has received great attention in the field of wearable and healthcare technologies. To realize such a unique technology typically on a single platform, it is very crucial to adopt highly-flexible and embeddable energy storage devices with adequate efficiencies as power sources. In this direction, we introduce a versatile and scalable approach to fabricate planar and symmetric micro-supercapacitors, which can be mounted on any complicated surface. The micro-supercapacitors developed on highly flexible and ultrathin substrates by the angular spray of graphene-ink showed excellent performance with a maximum areal capacitance of ~8.38 mF/cm 2 and operating flexibility for a bending radius of 1.8 mm. The devices also displayed outstanding mechanical stability for 10, 000 bending cycles with a high specific capacitance (~22 F/g) and power density (~1.13 kW/kg) typically at a scan rate of 100 mV/s. Further, the demonstrations on skin-mountable and wrappable characteristics of mSCs emphasized their adaptability as embeddable power sources for various epidermal and wearable devices. Graphical abstract: Image 1 Highlights: Micro-supercapacitors fabricated using cost-effective spray method. Device exhibits high energy density and excellent sustainability. Extremely flexible micro-supercapacitor showed high mechanical durability and stability. Our device developed on epidermal substrate showed integrability with human skin. This micro-supercapacitors can greatly support for e-skin device as a power source.